Investigation of potential prognostic biomarkers for colorectal cancer - Hui Li; Jie Liu; WenHui Liu; Liang Zheng; JuHui Chen (Archives of Medical Science)
Introduction Colorectal cancer (CRC) is the third leading cause of cancer-related death. Since CRC is largely asymptomatic until the alert features develop to an advanced stage, implementation of a screening program is important to reduce cancer morbidity and mortality. Current screening methods have significant limitations.